Exostose and Osteomata Prevalence in Portuguese Navy Divers - d'Espiney Amaro, Carla (2008)
Objective: To determine the prevalence of exostoses and osteomata in the Portuguese Navy divers and its relation with the years of diving, age and immersion time.Patients and Methods: One hundred forty nine patients were included in the study. The study group (Group A) was formed by 87divers and the contrai group (Group 8) was formed by 62 individuais that have never dived. A clinical history and otoendoscopy was taken to ali individuais. The exostoses were classified in three grades according to the percentage of obstruction within the externa/ auditory canais.Results: Both groups were uniform in age and sex. There were 86% of divers with exostoses in one or both ears in group A and 43.6% had 1 or more osteomata. With chi-square test it was established a significant difference (p<0.05) in exostoses prevalence between the two groups.Conclusions: ln this study, diving was significant in exostose andosteomata prevalence.